2000
DOI: 10.1097/00001888-200002000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Programs for the Development of Physician Leaders

Abstract: Physician leaders are crucial as never before to ensure the proper integration of good care and cost containment; such integration is both a reasonable expectation of patients and essential for the survival of health care delivery systems. In today's health care environment, a critical mass of physician leaders must be developed in a systematic fashion so that physicians may truly lead the health care enterprise. The authors (1) describe, with examples, the various types and levels of physician leadership trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…Hospitals have also reported success in cultivating emotionally intelligent leadership in different hospital improvement and quality care interventions. 34,35,73,[93][94][95] EI has been used as a framework for leadership development in wide-ranging specialty practices [96][97][98] and in primary care. 99,100 A key feature of these interventions is that they were implemented across hospital systems.…”
Section: Leadership Development Practices and Models Of Ei Varymentioning
confidence: 99%
“…Hospitals have also reported success in cultivating emotionally intelligent leadership in different hospital improvement and quality care interventions. 34,35,73,[93][94][95] EI has been used as a framework for leadership development in wide-ranging specialty practices [96][97][98] and in primary care. 99,100 A key feature of these interventions is that they were implemented across hospital systems.…”
Section: Leadership Development Practices and Models Of Ei Varymentioning
confidence: 99%
“…33 Finally, in a systematic review of available reports, Stoller 26 has suggested six domains of needed competencies as those that characterize effective physician-leadership, including: technical knowledge (i.e., of operations, finance and accounting, information technology and systems, human resources (including diversity), strategic planning, legal issues in health care, and public policy), knowledge of health care (i.e., of reimbursement strategies, legislation and regulation, quality assessment and management), problem-solving prowess (i.e., around organizational strategy and project management), emotional intelligence (i.e., the ability to evaluate self and others and to manage oneself in the context of a group), communication (i.e., in leading change in groups and in individual encounters, such as in negotiation and conflict resolution), and a commitment to lifelong learning. As pointed out in these and other available reports, [22][23][24][25][26] even with significant initial efforts to clarify the needed competencies and to offer programs that attempt to cultivate these skills among emerging physician-leaders, 7,[22][23]26 several basic, pressing questions remain that mandate this call to action. For example, what is the evidence that acquiring these competencies ties to better organizational and/or personal performance?…”
Section: The Rationale For Developing Physician-leadersmentioning
confidence: 99%
“…Though developing great leaders and embracing change are well-established characteristics of frontrunner organizations in many industry sectors, health-care institutions have generally lagged behind and are just recently awakening to the importance of developing physician-leaders. 7 This perspective addresses the rationale and need for developing physicianleaders.…”
Section: Introductionmentioning
confidence: 99%
“…There are also many venues for more formal training that are valuable and can be tailored to your needs 10 .…”
Section: Personal Developmentmentioning
confidence: 99%